A cryptographic use indicator matrices systems Walsh functions - Белецкий, Анатолий Яковлевич (Ukrainian Information Security Research Journal, 2016)
The article deals with the formation and application of cryptographic systems, symmetric Walsh functions binary power order. A synthesis system is based on their indicator matrices. The indicator is right-sided symmetric (0,1)-matrix, i.e. matrix, symmetric with respect to the auxiliary di-agonal, non-degenerate in the ring of residues modulo 2. The order of test matrices is a logarithmic dependence on the order of the Walsh system. The decision marked the problem of the synthesis of the so-called direct problem Walsh. The inverse problem is that for a given matrix of Walsh matrix to calculate its tally. The problem of the development of algorithms for cryptographic protection of video packets transmitted over the air on board unmanned aircraft. Kripto transform reduced to a two-dimensional fast Fourier transform in the basis of the video systems Walsh functions are protected from unauthorized access. Establishes the right permutation counts discrete input signal processor FFT calculates the spectrum of the signal in a given basis Walsh functions